EFFICIENT UTILISATION OF AUTOMATION IN CONSTRUCTION MATERIALS-HANDLING ROCESSES - Okonkwo, Grace Chinyere (Ayden International Journal of Banking, Finance and Technology, 2025)
There is a limited understanding of automation in construction materials-handling processes utilized by manufacturing firms in Nigeria. This article evaluates the level of utilization of automation in construction materials-handling operations by manufacturing firms in North-Central Nigeria, to improve operational efficiency and reduce operating costs. Using a case study research design, quantitative data (observation guide with measurements) were collected from 32 purposively selected construction material manufacturers. A total of 72 customers’ orders were observed and recorded to be representative of deliveries from the sampled (n=32) manufacturers’ warehouses to other terminals. The descriptive method of data analysis was employed using percentages and results presented in a form of bar charts. The study reveals low-level utilization of automation in the combined processes of order picking, storage, loading, and offloading of material. These imply increasing material costs and causing a delay in delivery. The article concludes by providing construction-material manufacturers with areas that require automation to optimize material-handling Operations. A recommendation is made for further study to explore why automation is not utilized despite its advantage